Project Financing in Laos’ Hydropower for Export of Electricity to Thailand - Phomsoupha, Xaypaseuth (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
Laos, a mountainous and landlocked country, continues to exploit its hydropower potential for export of electricity to neighboring countries such as Thailand, Vietnam and Cambodia. Despite the great development potential and market opportunities both inside and outside the country, the scarcity of finance for public investment in the power generation sector has been a bottleneck for Lao hydropower. Private investment has therefore been sought and promoted through an independent power producer (IPP) approach which relies on the availability of project funds from the private sector. Currently, six privately-financed hydropower projects operated by private companies are exporting electricity to the grids of Laos’ neighbors. Ten additional hydropower projects developed with private financing are now under construction, and several other projects now under consideration as to their technical feasibility are planned to achieve power-on by 2020. DOI: http://dx.doi.org/10.3126/hn.v10i0.7096 Hydro Nepal Vol.10 January 2012 7-10